The jubilee of the Editor-in-chief of the «Journal of NBC Protection Corps», Dr. Techn. Sciences, Lenin Prize winner (1991), Col.-Gen. (Ret.) Stanislav Veniaminovich Petrov, Chief of the USSR Chemical Troops (1989–1991), Chief of the NBC Protection Troops of the Russian Federation (1992–2001) - article Editorial (Вестник войск РХБ защиты)
.